How do technological innovation and urbanization drive economic growth in Tanzania and transform societies? Exploring the potential channels - Mwoya Byaro; Anicet Rwezaula (Journal of Economy and Technology)
The current era is witnessing a rapid pace of technological innovation and accelerated urbanization globally. This study examines the impact of technological innovation (trademark registrations) and urbanization on economic growth in Tanzania from the period 2002–2021 while accounting for inflation and industrialization in the regression model. Estimation is done using Kernel Regularized Least Squares (KRLS), a machine-learning technique. Results show that technological innovation has a positive impact on economic growth, with an average increase of 0.03 %. Inflation has a negative impact; reducing economic growth by 0.02 %. Urbanization and industrialization have positive impacts, increasing economic growth by 0.58 % and 0.16 %, respectively. Further, the study shows that the average increase in technological innovation (trademark registrations) leads to a 0.01 % increase in economic growth at the 50th percentile and a 0.16 % increase at the 75th percentile. However, at the 25th percentile, technological innovation reduces economic growth by 0.05 %. Conversely, the average increase in urbanization increases economic growth by 0.38 %, 0.61 %, and 0.83 % at the 25th, 50th, and 75th percentiles, respectively. Robustness tests confirm that technological innovations and urbanization promote economic growth in Tanzania. The study discusses the potential channels through which technological innovation and urbanization influence economic growth in Tanzania and transforms society, and provides practical policy implications.